MODEL PENGELOLAAN DANA HAJI DI BANK SYARIAH - Ifa Hanifia Senjiati (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2017)
Hajj is one pillars of Islam which must be implemented by every muslim who has capability. Capability must be fulfilled is ability to pay costs of Hajj Organizers (BPIH). BPIH managed by the Ministry of Religious Affairs through several financial instruments such as savings, deposits and sukuk. The efficient and effective management of funds Haj is through sharia banks with the dinar as a instrument of payment cause dinar as currency of Islam that has advantages than fiat money. The objective of the research is to decribe model of management funds haj in sharia banking by dinar and to know what is the multifiler effect from its model. This study uses qualitative research based on studies litelatur, which is sourced from books, internet, and other documents that support this research. Result of this study is showing model of management funds haj by synergy function of sharia bank like funding (receive deposit and saving dinar also costs of hajj), lending (to the BMT of mosque) and charity (lend the zakat to mustahiq). This model gives multiflier effects like BPIH price will fall, the growth of new entrepreneurs through BMT program eco-mosque, socialize use dinar, and preventing corruption.